Fascism, corporatism and the crafting of authoritarian institutions in inter-war european dictatorships - Pinto, António Costa (2015)
The diffusion of political and social corporatism, which with the single-party are hallmarks of the institutional transfers among European dictatorships, challenges some rigid dichotomous interpretations of interwar fascism. This chapter rethinks the role of corporatism as a political device against liberal democracy and especially as a set of authoritarian institutions that spread across inter-war Europe and which was an agent for the hybridization of the institutions of fascist-era dictatorships. We argue that corporatism was at the forefront of this process of cross-national diffusion, both as a new form of organized interest representation and as an authoritarian alternative to liberal democracy.